Genetic variation of the human ACE and ACTN3 genes and their association with functional muscle properties in Lithuanian elite athletes - Gineviciene, V.; Pranculis, A.; Jakaitiene, A.; Milasius, K.; Kucinskas, V. (Medicina, 2011)
Background and Objective. Based on the results of many studies, the angiotensin-converting enzyme (ACE) and the a-actinin-3 (ACTN3) genes are considered strong candidate genes associated with human physical performance. On the other hand, the data regarding the association of the ACE I/D and ACTN3 R/X polymorphisms with human physical performance in different populations have been conflicting. The objective of our research was to evaluate the significance of these genetic variants on muscle performance phenotype in Lithuanian athletes.